A Thematic Review on Exploring Ethnoscience in Science Education: A Case in Indonesia - Kasi, Yohanes Freadyanus; Samsudin, Achmad; Widodo, Ari; Riandi, Riandi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This study aims to review the ethnoscience studies in science education in Indonesia thematically. From 2010 to 2020, the databases contained 71 relevant articles of ethnoscience studies. These studies belonged to the content analysis theme parameters of method/design, sample, data collection, data analysis, topic, result, recommendation, and location. The results indicated that most of the ethnoscience studies explored the effect of integrating ethnoscience with the lessons to investigate students’ achievement and attitudes towards science. Correspondingly, the investigated studies mostly used Research and Development (R & D) and experimental research design. The preferred data collecting techniques were tests (multiple-choice/description), questionnaires, and observation. Moreover, seventh and eighth graders of junior high school commonly employed the argumentation activities in physics, chemistry, biology, and basic concept of science topics. This study suggests the teachers employ different methods (e.g., ethnoscience) to improve concept understanding, problem-solving skills, critical thinking skills, and motivation in learning science from the primary school level. Furthermore, resources from cultural activities in Indonesia are beneficial for integrating ethnoscience in learning.